THE SCALE INSECTS OF IRAN (HEMIPTERA: COCCOMORPHA)PART 2 THE MEALYBUGS (PSEUDOCOCCIDAE AND RHIZOECIDAE) AND PUTOIDAE - Moghaddam, Masumeh; Watson, Gillian W. (Zootaxa, 2022)
Iran is situated at the junctions of the Palaearctic and Oriental zoogeographical Regions, and the Caspian, Baluchi and Irano-Turanian floral zones, so it has a very diverse scale insect fauna. Scale insects (Hemiptera: Coccomorpha) are economically important in forestry, agriculture and horticulture. This taxonomic work on the mealybugs (Pseudococcidae and Rhizoecidae) and Putoidae of Iran is the second of three parts planned to cover all the scale insects (Hemiptera: Coccomorpha) in the country. It provides a resource for accurate laboratory identification of all the species known to occur in Iran or that are likely to be found there. Keys to the genera and species of mealybug found in Iran—29 genera and 62 species of Pseudococcidae, and one genus and one species in each of the families Rhizoecidae and Putoidae—are provided. Detailed line drawings of all the species are given to facilitate identification. These are accompanied by detailed descriptions, distribution data, information on natural enemies, economic importance and host-plants recorded in Iran. The main purpose of the work is to provide agricultural staff concerned with pest control and quarantine inspection in Iran with a reliable means of species identification. The species Dysmicoccus walkeri (Newstead), Peliococcus marrubii (Kiritshenko) and Phenacoccus transcaucasicus Hadzibejli are recorded for the first time from Iran, and Artemicoccus poacearum Moghaddam & Watson sp. n. and Spilococcus williamsi Moghaddam & Watson sp. n. are described.